Pengaruh Kompensasi Finansial, Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan - Achmad Alwi Ircham; Muhammad Mansur (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT                The purpose of this study was to describe financial compensation, leadership style, work motivation, and employee performance and to determine the effect of financial compensation, leadership style, and work motivation on employee performance partially or simultaneously. This research method uses quantitative methods. This type of research is explanatory research.The sample of this study is CV. Build Mitra Sarana by using saturated sampling, as many as 50 respondents. Data collection method uses a questionnaire. The analytical method used in this study is multiple regression analysis with SPSS 14.0 for windows.The results of this study indicate that: (1) There is a positive and significant effect of financial compensation on employee performance CV. Bangun Mitra Sarana. (2) There is a positive and significant influence on leadership style on the performance of employees of CV. Bangun Mitra Sarana. (3) There is a positive and significant influence on work motivation on employee performance CV. Bangun Mitra Sarana. Keywords: Financial Compensation, Leadership Style, Work Motivation and Employee Performance.